Free-standing flexible nanocrystalline-ZnO-impregnated polyvinylidene fluoride composite thin films. (October 2015) - Bhunia, R; Ghosh, D; Ghosh, B; Hussain, S; Bhar, R; Pal, AK
Free-standing flexible films of nanocrystalline ZnO impregnated polyvinylidene fluoride composites were prepared by sol-gel technique. Effect of ZnO loading on the optical properties of the polyvinylidene fluoride host matrix was studied critically for the as-deposited as well as the poled samples. Bonding environment was studied by X-ray photoelectron spectroscopy and Fourier transformed infrared spectroscopy measurements. Modulation of optical and microstructural properties with ZnO loading was also addressed.